Child stunting and lack of chronic energy of pregnant women: specific nutritional intervention of 1000 HPK movement at Puskesmas - Anita, Dewi Nur (BKM Public Health and Community Medicine, 2021)
The critical period for the growth and development of a child which is called the First 1000 Days of Life is influenced by the nutritional status of the mother during pre-pregnancy, pregnancy and during breastfeeding. Nutritional problems that can occur during this period are stunting (short). One of the programs included in the First 1000 Days of Life Movement (HPK) in an effort to prevent stunting is a specific nutritional intervention. In implementing the 1000 HPK program, there are several causes of stunting problems and lack of nutritional status in pregnant women, namely direct and indirect causes. Puskesmas has two problems that need to be resolved related to nutritional intake and health status with the success of the program, namely the provision of PMT. There are several factors that hamper the success of the program, including limited nutritionists, no guidelines and SPO on handling growth faltering, the planning process has not been carried out in a button up and not all specific nutrition interventions have recorded reporting. However, it is also a priority in the health center area to be able to reduce problems with indirect causes, including food security, social environment, health environment, and residential environment (Bappenas, 2018). Social support encourages mothers to get balanced nutrition during pregnancy. Inviting and involving pregnant women and their families to actively participate in managing the productive economy so that family income increases. In addition, the local government can increase the budget for nutritious feeding to pregnant women during ANC activities.